2003
DOI: 10.1002/nme.604
|View full text |Cite
|
Sign up to set email alerts
|

Stress intensity factor analysis of interface cracks using X‐FEM

Abstract: SUMMARYThe extended ÿnite element method (X-FEM) proposed by Belytschko et al. (International Journal for Numerical Methods in Engineering 1999; 45:602;1999; 46:131; 50:993) uses interpolation functions based on the concept of partition of unity, and considers the asymptotic solution and the discontinuity of displacement ÿelds near a crack independently of the ÿnite element mesh. This paper describes the application of X-FEM to stress analyses of structures containing interface cracks between dissimilar mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(74 citation statements)
references
References 26 publications
0
74
0
Order By: Relevance
“…Since the early works, the stress intensity factors have been computed by the domain form of the J-integral, [75,32,52,79]. Liu et al [68] proposed a direct evaluation of the stress intensity factors, based on enrichment functions expressed in terms of stress intensity factors.…”
Section: Literature Review On Crackmentioning
confidence: 99%
“…Since the early works, the stress intensity factors have been computed by the domain form of the J-integral, [75,32,52,79]. Liu et al [68] proposed a direct evaluation of the stress intensity factors, based on enrichment functions expressed in terms of stress intensity factors.…”
Section: Literature Review On Crackmentioning
confidence: 99%
“…To measure the initial load, four stain gauges were attached vertically in front of the precast notch on the both sides of specimen, and the distance of two strain gauges was 10 mm. The experimental setup for TPB test is shown in The displacement extrapolation method [5] was used to calculate the stress intensity factors (SIFs) K 1 and K 2 of bi-materials interface crack through relative crack surface displacements δ x and δ y. It should be noted that stress intensity factors K 1 and K 2 can be denoted as ini 1 K and ini 2 K , which are the initial fracture toughness, when δ x and δ y are caused by initial load.…”
Section: 65mentioning
confidence: 99%
“…In the case of bimaterial interface cracks, the complex SIFs, gained by dint of the displacement correlation technique, are related by (see [18]…”
Section: Solution To Biomaterials Interface Cracks [15]mentioning
confidence: 99%
“…It has been demonstrated that a global strain of 1% already integral methodology is grounded on the superposition of two equilibrium states, formulated by the current problem and a set of auxiliary known solutions. The procedure has been recently announced in a number of papers using FEM to calculate stress intensity factors along three-dimensional interface cracks [8,9]. In the field of fracture mechanics the solution to the applications of very interest is facilitated by using a multi-domain technique grounded on the boundary contour method [15].…”
Section: Introductionmentioning
confidence: 99%